Implementasi Circular Economy pada Rumah Inovasi dan Daur Ulang Bank Sampah Nusantara Pondok Pesantren Al Ihya Ulumaddin Kesugihan Cilacap - Afifudin Zuhdi; Fitria Nurul Azizah (CV. Syntax Corporation Indonesia, 2022)
This paper describes the implementation of the circular economy at the Innovation and Recycling House of the Nusantara Garbage Bank at the Al Ihya Ulumaddin Kesugihan Islamic Boarding School in Cilacap which was carried out by students of the Al Ihya Ulumaddin Kesugihan Islamic Boarding School at Cilacap. This paper uses a qualitative method with a field research approach. This paper emphasizes 5 models of waste management, namely (Reduce, Reuse, Recycle, Replace, Repair) which are implemented in a circular economy system.